High-Temperature Fermentation and Its Downstream Processes for Compact-Scale Bioethanol Production - Sornsiri Pattanakittivorakul; Izumi Kumakiri; Pumin Nutaratat; Marino Hara; Morihisa Yokota; Masayuki Murata; Tomoyuki Kosaka; Pornthap Thanonkeo; Savitree Limtong; Mamoru Yamada (Fuels)
High-temperature fermentation (HTF) of ethanol can reduce costs of cooling, sterilization, and related equipment compared to the costs of general ethanol fermentation. To realize HTF, however, there are various issues to be considered, such as the fermentation temperature upper limit for ethanol-producing thermotolerant yeast, the size of a fermenter that does not require cooling, and the effective temperature for suppressing microbial contamination. This study focused on these issues and also on downstream processes that exploit the advantages of HTF at temperatures exceeding 40 °C. The permissible size of a fermenter without cooling was estimated by simulating heat generation and heat dissipation. Fermentation productivity at high temperatures when using the thermotolerant yeast Kluyveromyces marxianus and the inhibitory effect of high temperatures on the growth of contaminant microorganisms were examined. After fermentation, the recovery and concentration of ethanol were performed by reduced-pressure distillation (RPD) and membrane separation. These experiments demonstrate that efficient HTF can reduce the amount of saccharifying enzymes in simultaneous saccharification and fermentation and can shorten the transition time from the saccharification step to the fermentation step in separate saccharification and fermentation, that RPD at fermentation temperatures enables a smooth connection to the HTF step and can be performed with a relatively weak vacuum, and that membrane separation can reduce the running cost compared to the cost of general distillation on a compact scale.